Demand and supply of technical vocational education and training (TVET) in the Autonomous Region in Muslim Mindanao (ARMM) - Orcullo, Zela Amor A.
The study was designed to assess the status of the Technical Vocational Education and Training (TVET) sector in the Autonomous Region in Muslim Mindanao (ARMM). The research tried to look into the causes of the existing skills mismatch in ARMM. The analysis was done by examining both the demand for and the supply level of TVET in ARMM. Direct demand, which refers to the tit in/ demand for skills in the region, and derived demand, as represented by the students' enrollment for TVET programs, were analyzed. Direct supply of TVET, or the number of TVET graduates, and the derived supply, as denoted by the number of TVET providers, was also examined. Secondary data analysis was conducted. This was complimented by conducting key informant interviews among various stakeholders in the area. The secondary data were gathered from the RPDO- ARMM, RBOI- ARMM. National Statistics Office, and TESDA- ARMM. Relevant information regarding the factors affecting demand for and supply of TVET were included in the analysis. The causes of mismatch were inferred from the analysis of secondary data and the results of the conducted survey. Moreover, a correlation analysis was employed in this study to further validate the findings using secondary data. The results showed that much of the mismatch is due to the current situation wherein an agricultural economy produces a labor force belonging to the non- agric sector. Another significant factor affecting mismatch is the tact that ARMM produces new graduates every year despite the very low investment level in the region. Issues and policies concerning the TVET providers, students and related institutions, were also discussed as part of the analysis.